One-pot synthesis of IrNi@Ir core-shell nanoparticles as highly active hydrogen oxidation reaction electrocatalyst in alkaline electrolyte. (May 2019) - Liu, Di; Lu, Siqi; Xue, Yanrong; Guan, Zhi; Fang, Jinjie; Zhu, Wei; Zhuang, Zhongbin
Abstract: Highly active and low cost hydrogen oxidation reaction (HOR) catalysts for anion exchange membrane fuel cells are desired, because the HOR catalytic activity under alkaline condition is much slower than that in acid. Herein, a novel and efficient IrNi@Ir core-shell HOR catalyst was synthesized by a simple one-pot approach using both iridium acetylacetonate and iridium chloride as the Ir sources, beneficial from their different reactivities. The hydrogen binding energy of the surface Ir shell is tuned by the IrNi alloy core, leading to the promoted HOR activity and stability. The mass activity of IrNi@Ir/C is 1.12 mA mg Ir − 1 at 0.05 V in 0.1 M KOH, which is 2.4 times that of Ir/C, and also higher than that of commercial Pt/C. It demonstrates that the fine-tuned nanostructure is propitious to the catalytic performance and has potential applications in the future clean energy device. Graphical abstract: fx1 Highlights: IrNi@Ir core-shell nanoparticles have been synthesized through a simple one-pot method by using two iridium sources. The obtained IrNi@Ir core-shell nanoparticles show high activity towards hydrogen oxidation reaction in alkaline condition. The enhanced hydrogen oxidation reaction activity comes from the uniform Ir shell tuned by the IrNi alloy core by the electronic effect.